Molecular dynamics simulations of the lyotropic reverse hexagonal (HII) of Guerbet branched-chain β-d-glucoside - Nguan, H.; Ahmadi, S.; Hashim, Rauzah (Royal Society of Chemistry, 2013)
Through atomistic molecular dynamic simulations using a GROMOS53a6 force field for the carbohydrate, we studied the lyotropic reverse hexagonal phase HII from a glycolipid, namely the Guerbet branched-chain β-d-glucoside, at 14% and 22% water concentrations. Our simulations showed that at low water concentration (14%) the sugar head group overlapped extensively and protruded into the water channel. In contrast, in the 22% concentration system a water column free from the sugar headgroup ('free' water) was formed as expected for the system close to the limit of maximum hydration. In both concentrations, we found anomalous water diffusion in the xy-plane, i.e. the two-dimensional space confined by the surface of the cylinder. On the other hand, along the z-axis, the water diffusion obeyed the Einstein relation for the 22% system, while for the 14% system it was slightly anomalous. For the 22% system, the diffusion along the z-axis of the 'free' water obeyed the Einstein relation, while that of the 'bound' water is slightly anomalous. The xy-plane displacement of the 'bound' water was higher than that for the 'free' water at times longer than 200 ps, as a consequence of the exchange of water molecules between the two regions. Based on our findings, we proposed an alternative explanation to the observed spatial heterogeneity in the HII phase from probe diffusion by Penaloza et al. (Phys. Chem. Chem. Phys., 2012, 14(15), 5247-5250). We found the extent of contact with water was different at different oxygen atoms within the sugar ring. Generally, a higher probability of hydrogen bonding but a shorter lifetime was found in 22% water compared to the case of 14% water. Finally, we examined the extension and compression of the alkyl chain of a columnar.